GOOD HYGIENE PRACTICES AS AN IMPORTANT PROGRAM FOR SAFETY OF FINAL PRODUCTS - Ljubica TRAJKOSKA (Stefan cel Mare University of Suceava, 2021)
In order to meet the requirements regarding food safety, in addition to the HACCP system, food operators are required to adopt, implement and document Good Hygiene Practice (GMP), Good Manufacturing Practice (GMP), Standard Operating Procedures (SOP) and Standard Sanitary Operating Procedures (SSOP). Therefore, the purpose of our research was to determine the importance of implemented hygienic and manufacturing practices in the meat industry in the municipality of Prilep. Analysis of the sensory, physicochemical and microbiological parameters of water, as well as the presence of Listeria monocytogenes on the contact surface and in thin sausage (vacuum packed) was performed. The results of the water analysis show that it is safe and does not lead to additional contamination of sausages. In addition, the absence of Listeria monocytogenes is a result of well-established practices regarding the microbiological quality of sausages.